Pola Komunikasi Majelis Mujahidin Sumatera Utara dalam Mensyiarkan Syariat Islam di Kota Medan - Prabu, Muhammad Rizky; Ritonga, Hasnun Jauhari; Bahri, Andini Nur (YASIN, 2023)
The purpose of this study was to determine the communication patterns of the mujahidin assembly in broadcasting Islamic syari'at in the city of Medan and to determine the inhibiting factors and supporting factors of the mujahidin assembly in broadcasting Islamic syari'at in the city of Medan. The method in this study was to use a qualitative method where the researcher directly interviewed the informants or informants face to face in this study. The results of this study are the communication patterns of the Mujahidin Council in broadcasting Islamic Shari'at in Medan City which are carried out in several ways, namely circle patterns, wheel patterns, Y patterns and other communication patterns and also in this communication pattern there are also methods in this communication pattern and also there are several stages of communication patterns, namely planning, implementation and evaluation. Obstacle factors in the communication patterns of the Mujahidin Council in broadcasting Islamic Shari'at in Medan City lack of facilities at the mujahidin assembly, language factors that are not mastered and also distance factors and supporting factors in communication, there are supporting factors, namely the message conveyed is appropriate and can be received and understood by the people of Medan City, there is also direct feedback because you get a good and fast response there is also an evaluation where in evaluating this message the recipient and sender or the sender can receive it directly so that a mature dialogue occurs. Therefore, if this evaluation is synchronous, it will lead to a common understanding in interpreting the message.